Ekonomi Digital dan Inovasi Teknologi: Menilai Pengaruhnya terhadap Produktivitas Bisnis - Ririn Syahfitri; Haifah Ilmi; Widodo Sihotang (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to analyze the effect of the digital economy and technological innovation on business productivity, focusing on the relationship between the level of digital technology adoption and productivity improvements in various industrial sectors. Based on linear regression analysis of data obtained through surveys and secondary data, the results show that the adoption of digital technologies, such as artificial intelligence (AI), big data, and the Internet of Things (IoT), significantly increases business productivity, especially in sectors that are more connected to advanced technologies, such as e-commerce, banking, and manufacturing. In contrast, sectors that are more conservative in technology adoption, such as agriculture and healthcare, show more limited productivity gains. These findings emphasize the importance of managerial support, human resource readiness and adequate technological infrastructure in supporting the successful adoption of digital technologies. Limitations of this study include limited sample coverage and short-term impact measurement, which warrant further research by expanding the sample and observation time. The policy implication for the government is the importance of supporting digital infrastructure development and HR training, while for businesses, this study recommends the importance of creating a culture of innovation and sustainable digital transformation.